Exploration of Local Culture as a Learning Resource in STEAM Learning - Nur Ismirawati; Nur Zakiyah Randi; Andi Jusman Tharikh (Al Jahiz, 2025)
Integrating local cultural elements into education represents a strategic approach to preserving cultural heritage while increasing student engagement in understanding science, technology, engineering, art, and maths (STEAM) concepts. This research employed a qualitative case study approach, conducted in schools in Pangkep Regency. Data were collected through interviews with educators and cultural experts, participatory observations, and document analysis, while the findings were examined using thematic analysis. The objectives of this study are threefold: firstly, to identify local traditional games that can be integrated into STEAM learning; secondly, to analyze their impact on students' cognitive and social skills; and thirdly, to propose effective implementation strategies. The study's results demonstrated that traditional games such as Gandrang Bulo, Magasing-gassing, and Enggo-enggo possess considerable educational potential, enhancing science literacy and motor skills and fostering cultural identity and cooperative learning. However, it is crucial to acknowledge the challenges posed by limited educational resources and teacher readiness, which must be surmounted for the successful implementation of this approach. The study proposes the formulation of a structured curriculum that integrates these cultural elements, to enrich STEAM learning and foster a more profound appreciation of local cultural heritage among students.